2018
DOI: 10.1080/15592324.2018.1513298
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for PsbO1 in photosynthetic electron transport as suggested by its light-triggered selective nitration inArabidopsis thaliana

Abstract: Exposure of Arabidopsis leaves to nitrogen dioxide (NO) results in the selective nitration of specific proteins, such as PsbO1. The 9th tyrosine residue (Tyr) of PsbO1 has been identified as the nitration site. This nitration is triggered by light and inhibited by photosynthetic electron transport inhibitors. During protein nitration, tyrosyl and NO radicals are formed concurrently and combine rapidly to form 3-nitrotyrosine. A selective oxidation mechanism for Tyr of PsbO1 is required. We postulated that, sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…This buffer contained NO 2 and NO 2 − as nitrating agent [61]. As it is reported that nitrite anion inhibits PSII to decrease oxygen evolution [72,73,74], it is necessary to separately evaluate these two effects of nitrite on the oxygen evolution. Thylakoid membranes isolated from Arabidopsis leaves were incubated in a buffer containing NO 2 and NO 2 − or a buffer containing NO 2 − alone in the light or in the dark [71].…”
Section: Psbo1 May Function As An Electron Element Like Yz In Psiimentioning
confidence: 99%
“…This buffer contained NO 2 and NO 2 − as nitrating agent [61]. As it is reported that nitrite anion inhibits PSII to decrease oxygen evolution [72,73,74], it is necessary to separately evaluate these two effects of nitrite on the oxygen evolution. Thylakoid membranes isolated from Arabidopsis leaves were incubated in a buffer containing NO 2 and NO 2 − or a buffer containing NO 2 − alone in the light or in the dark [71].…”
Section: Psbo1 May Function As An Electron Element Like Yz In Psiimentioning
confidence: 99%